Isolation and studies of a thioether-functionalized pyrazole derived Cu(i)-based cyclic trinuclear complex and its coordination polymers with [Cu2I2] and [BiBr3] nodes. Issue 32 (2nd August 2021) - Lin, Zhi-Qing; Zheng, Sai-Li; Hu, Jieying; Zhou, Hua-Qun; Feng, Zihao; He, Yonghe; Chung, Lai-Hon; He, Jun
Abstract : Emissive Cu(i )-CTC with unprecedented thioether SBUs have their photoluminescence shifted and quenched after assembly with CuI and BiBr3, respectively. Abstract : Cu(i )-based cyclic trinuclear complexes (CTCs) represent one of the most intensively investigated candidates in coinage metal-derived CTCs because of their rich photoluminescence properties. Beyond the molecular level, coordination polymers built upon Cu(i )-based CTCs have developed rapidly in recent times. However, most of the secondary building units (SBUs) on pyrazolyl moieties reported to-date have been centralized on pyrazoles, pyridines and carboxylates and most of the nodes for bridging linkers have been based on copper-halide clusters. This work presents the use of a thioether-functionalized pyrazole to construct Cu(i )-based CTC, 1, which was allowed to react with CuI and BiBr3 for constructing coordination polymers, 2 and 3, respectively. Successful isolation of 2 and 3 highlights that the thioether pendant on the pyrazole can act as a novel class of SBUs on Cu(i )-based CTCs to assemble coordination polymers with a soft Lewis acid and not limited to copper-halide clusters.